2021
DOI: 10.3390/agriculture11100952
|View full text |Cite
|
Sign up to set email alerts
|

Estimations on Trait Stability of Maize Genotypes

Abstract: The purposes of this study were to define the kind of trait inheritance through stability estimations of various traits in maize, to define the relationship between different environments and maize hybrids, and to propose the best environments and hybrids for farmers. Field experiments were conducted in two years (2011 and 2012) at four different locations in Greece: Florina, Trikala, Kalambaka and Giannitsa which were selected as they represent different environments. The genetic materials tested in a Randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Using molecular markers and clustering, Alzahrani et al [4] managed to separate cultivars According to the ANOVA table, G × E interactions were highly significant in our research. Greveniotis et al [24][25][26][27]46,47] reported that G × E interactions often occur in the cultivations of many plants aiming to support livestock, meaning different behavior in different places or years. The main traits of alfalfa breeders and farmers, taking into account green mass yield, dry matter yield, and protein content (%), are subjective to GEI [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using molecular markers and clustering, Alzahrani et al [4] managed to separate cultivars According to the ANOVA table, G × E interactions were highly significant in our research. Greveniotis et al [24][25][26][27]46,47] reported that G × E interactions often occur in the cultivations of many plants aiming to support livestock, meaning different behavior in different places or years. The main traits of alfalfa breeders and farmers, taking into account green mass yield, dry matter yield, and protein content (%), are subjective to GEI [5].…”
Section: Discussionmentioning
confidence: 99%
“…The stability index was calculated using, as follows, [24][25][26][27]38,[43][44][45][46][47]] (x/s) 2 , where x represents the mean value of each parameter examined for every genetic material utilized in this study and s the respective standard deviation. ANOVA was used to assess the data across environments to reveal significant differences for each measured parameter.…”
Section: Data Elaborationmentioning
confidence: 99%
See 1 more Smart Citation
“…The predictive accuracy of such research trials is described in previous work based on AMMI analyses [ 22 ]. It is essential to depict that all analysis methods must be properly selected for each kind of data, including raw data and stability indices [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the main scope was to determine the forage yield stability of pea genotypes along with various correlated traits based on the innovative approach of estimating the stability index, with the specific aim of studying pea genotypes’ behavior under both conventional and low-input cultivation systems. Greveniotis et al [ 23 , 39 ] used a stability index, based on Fasoulas [ 7 ] and Fasoula [ 8 ] remarks, as an estimation of the heritability of various traits, leading to clear discrimination between qualitative and quantitative traits. Our approach includes stability performance analysis and reveals the stability performance and the kind of heritability of traits.…”
Section: Introductionmentioning
confidence: 99%